Dom Polski z okazji poświęcenia - 24 maja 2012 roku (Kronika Bydgoska, 2012)
On the initiative of the parish priest of the Bydgoszcz Fara Church - priest Tadeusz Skarbek-Malczewski, the Polish House, also called the Catholic House, was constructed in 1927. The building was officially consecrated on March 11, 1928. In accordance with the will of the originator, the House was designed for ‘all associations and people propagating social justice, loving God and the Motherland’. During World War Two, the Catholic House was burnt down. Right after the war, it was reconstructed, and opened again in 1947. On November 18, 1950, a semi-public chapel was erected here, which was to serve the religious and spiritual needs of the faithful and the clergy of Bydgoszcz city. In March 1961, the public Chapel of St Adalbert the Bishop and Martyr was erected. It was a place of church services for young people and the Catholic intelligentsia of Bydgoszcz city. In 1964, the First in Bydgoszcz Student Ministry Centre was located here. In 1971, when the Church of the Nuns of St Clare became the Student Church, church services with the participation of children and for the deaf-mute were concelebrated at the Catholic House. School religious instructions and class meetings were held here as well. From May 1982, this House was also a venue for lectures of the Primatial Institute of Christian Culture. In 2001, the Catholic House was closed down due to its bad technical condition. Nowadays, after rebuilding, it is used for the work of new evangelisation.